Leveraging Black pharmacists to promote equity in COVID‐19 vaccine uptake within Black communities: A framework for researchers and clinicians. Issue 8 (27th June 2022) - Abdul‐Mutakabbir, Jacinda C.; Simiyu, Brenda; Walker, Ramara E.; Christian, Robbie L.; Dayo, Yewande; Maxam, Meshell
Abstract: Black Americans are disproportionately represented among coronavirus disease 2019 (COVID‐19)‐related morbidities and mortalities. While the COVID‐19 vaccines are positioned to change this disparity, vaccine hesitancy, attributed to decades of systemic racism and mistreatment by the United States health care system, heavily exists among this racially and ethnically minoritized group. In addition, social determinants of health within Black communities including the lack of health care access and inequitable COVID‐19 vaccine allocation, further impacts vaccine uptake. Black pharmacists have worked to address the pandemic's deleterious effects that have been recognized within Black communities, as they are intimately aware of the structural and systematic limitations that contribute to lower vaccination rates in comparison to other racial and ethnic groups. Black pharmacists have been integral to promoting equity in COVID‐19 uptake within Black communities by disseminating factual, trustworthy information in collaboration with community leaders, advocating for the equitable access to the immunizations into vulnerable areas, and creating, low‐barrier, options to distribute the vaccines. Herein, we thoroughly explain these points and offer a framework that describes the role of Black pharmacists in narrowing vaccine equity gaps.